2004
DOI: 10.1007/s00213-003-1731-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic clozapine on d-amphetamine-induced disruption of auditory gating in the rat

Abstract: Qualitative differences between the idiopathic gating deficits observed in schizophrenic patients and AMPH-induced increases in T/C ratio in animals limit this models utility as a means of evaluating the ability of atypical antipsychotic drugs to restore normal sensory gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In the present study, we report behavioral as well as electrophysiological observations following sensory stimulation before and after several doses of the psychostimulant MPD. Most of the electrophysiological experiments investigating the property of MPD have been conducted in the presence of anesthesia [ 4 , 31 , 32 ], which is known to modulate CNS activity [ 33 ], or used brain slices [ 34 - 38 ] to record the effect of the drug on spontaneous activity and the role of different neurotransmitters in MPD action. None of the studies investigate, in freely behaving animals previously implanted with permanent electrodes and without the interference of anesthesia, the dose-response characteristics on sensory input recorded simultaneously from sites where psychostimulants are known to initiate and/or express their effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we report behavioral as well as electrophysiological observations following sensory stimulation before and after several doses of the psychostimulant MPD. Most of the electrophysiological experiments investigating the property of MPD have been conducted in the presence of anesthesia [ 4 , 31 , 32 ], which is known to modulate CNS activity [ 33 ], or used brain slices [ 34 - 38 ] to record the effect of the drug on spontaneous activity and the role of different neurotransmitters in MPD action. None of the studies investigate, in freely behaving animals previously implanted with permanent electrodes and without the interference of anesthesia, the dose-response characteristics on sensory input recorded simultaneously from sites where psychostimulants are known to initiate and/or express their effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have investigated the neurophysiological properties of psychostimulants, such as MPD, in intact humans or animals [ 30 ], especially its behavioral effects and alteration of sensory evoked neuronal activity in brain regions that are involved in the mesocorticolimbic DA system. Most neurophysiological studies that investigated psychostimulants have been conducted in vivo in the presence of anesthesia [ 4 , 31 , 32 ], which is known to interfere with CNS activity [ 33 ], or obtained in vitro on brain slices [ 34 - 38 ]. A valuable method to studying the mechanistic action of psychostimulants, such as MPD, on neuronal population is to record neuronal activity before and after administration of the psychostimulant in an intact, non-anesthetized, freely behaving subject through sensory-evoked field responses following sensory stimulation.…”
Section: Introductionmentioning
confidence: 99%
“… 65 , 76 Higher doses of clozapine, however, may improve gating by both decreasing S2 and increasing S1 amplitudes. 65 , 75 , 76 Human studies have mostly reported S1 increases after clozapine administration (Becker et al ; 80 Light et al; 133 Nagamoto et al ; 78 Nagamoto et al 79 ) although one study found that the drug decreased S2 amplitude (Adler et al 74 ).…”
Section: Hippocampal Gating As a Translational Tool: A Review And Evamentioning
confidence: 99%
“…In rodents, as in humans, sensory gating is usually measured as the ratio of the response amplitude to the first compared to the second stimulus (S2/S1). This ratio is often impaired in pharmacological models of schizophrenia targeting dopaminergic [43, 4851] and glutamatergic [38, 51] systems, with many studies suggesting that the increased ratio is due to a decreased S1 response [4951]. Although sensory gating has been tested in pharmacological animal models of schizophrenia, to our knowledge it has not been examined in NVHL rats.…”
mentioning
confidence: 99%